Cities: country development engines (2004)
This text gives consideration to the historical relationship between the city and the countryside, the main idea is propose a coherent relationship between the Latin American mayor cities and the not yet defined country role, towards the improvement of the nation’s destiny. The author calls attention on the fact that the cities grow disproportionately, without control or prevention on the impact to the environment, threatening the equilibrium city/countryside. In Venezuela, he considers the case of Caracas city and its closest regional system.